2021
DOI: 10.1016/j.ultrasmedbio.2021.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Can Predict the Clinical Course and Severity of COVID-19 Disease

Abstract: COVID-19 disease compromises the lung in large numbers of patients. The development of minimally invasive methods to determine the severity of the pulmonary extension is requested. This study aimed to describe the characteristics of sequential lung ultrasound and to test the prognostic usefulness of this exam in a group of patients admitted with COVID-19. We prospectively evaluated patients with SARS-CoV-2 infection admitted to our hospital between April and August 2020. Bedside lung ultrasound (LUS) exams wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Baseline diagnosis can cause several of the LUS findings, but the correlation of LUSS with FiO 2 needed, the differences between disease severity and ventilatory support groups, and the decrease with patient improvement show its usefulness as a monitoring tool. As shown by different publications, LUS is a useful tool in clinical examination and can quantify the loss of aeration at the bedside (29,30). Sequential assessments can help the clinician identify improvement or worsening; thus, they can be used to classify the severity of the disease and follow its progress (31).…”
Section: Discussionmentioning
confidence: 99%
“…Baseline diagnosis can cause several of the LUS findings, but the correlation of LUSS with FiO 2 needed, the differences between disease severity and ventilatory support groups, and the decrease with patient improvement show its usefulness as a monitoring tool. As shown by different publications, LUS is a useful tool in clinical examination and can quantify the loss of aeration at the bedside (29,30). Sequential assessments can help the clinician identify improvement or worsening; thus, they can be used to classify the severity of the disease and follow its progress (31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also assessed the dynamic changes in LUS findings during a COVID-19 infection and found that LUS can be used to monitor disease progression during hospitalization [ 1 , 19 , 20 ]. However, whether the LUS findings detected during the initial COVID-19 infection resolve or persist after hospital discharge is less well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The LUS score has shown to be highly sensitive in predicting ICU admission; every 1-point rise in LUS increases the odds of ICU admission by almost 50% ( 98 , 99 ). Patients admitted to the ICUs have higher LUS score on admission than those who did not require hospitalisation or were admitted to non-critical care wards ( 98 - 100 ), and all ICU patients had abnormal LUS findings on admission ( 101 ).…”
Section: Discussionmentioning
confidence: 99%